Current situation and prospects of Peruvian avocado (Persea americana) production in the context of international trade - Flores-Izquierdo, Manuel Antonio (2023)
This research aims to establish the current situation and prospects of Peruvian avocado production, in the context of international trade, using a non-experimental descriptive design. The production and export of Peruvian avocado remain on the rise, with positive forecasts. In 2021, the country harvested and exported 779 000 and 526 000 tons of avocado, respectively. By 2024, a 10 % growth in exports is expected compared to 2023, forecasting an export of 725 000 tons of fresh avocado. This increase is attributed to prior investments, the strong commitment of local producers, and the enhanced productivity of the fields. Regions such as La Libertad, Lambayeque, Ayacucho, and Huancavelica, among others, are key in production. Despite a challenging political context and adverse weather conditions in 2023, the industry managed to meet its estimates.